2016
DOI: 10.1155/2016/8163098
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration in the Virtual Hand Illusion with Active Movement

Abstract: Improving the sense of immersion is one of the core issues in virtual reality. Perceptual illusions of ownership can be perceived over a virtual body in a multisensory virtual reality environment. Rubber Hand and Virtual Hand Illusions showed that body ownership can be manipulated by applying suitable visual and tactile stimulation. In this study, we investigate the effects of multisensory integration in the Virtual Hand Illusion with active movement. A virtual xylophone playing system which can interactively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Sallnäs et al [7] found that implementing a force feedback mechanism had positive effects on physical presence and task performance. Similarly, haptic feedback showed positive effects on embodiment in VR [8].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Sallnäs et al [7] found that implementing a force feedback mechanism had positive effects on physical presence and task performance. Similarly, haptic feedback showed positive effects on embodiment in VR [8].…”
Section: Introductionmentioning
confidence: 87%
“…This method is mostly used when the illusion is induced passively only by stroking the hands without moving. We decided to consider proprioceptive drift even if, due to the problems with evaluating the drift in a active moving task as that proposed in this work, questionnaire are often used as the only mean to evaluate the strength of the illusion [8].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technical solutions applied in psychology-related literature are less sophisticated or do not represent the full capabilities of the human hand [25][26][27]. Moreover, the results on the influence of haptic feedback are contradictory [28,29]. Hence, it appears very promising to support psychological and biomechanical experiments targeting assisitve applications as well as the neuroscientific investigation on human sensory-motor control by a tailored robotic hand.Due to these reasons, a robotic hand concept designed to adopt the specific requirements appears very promising to support psychological and biomechanical experiments targeting assisitve applications such as prosthetics as well as the neuroscientific investigation on human sensory-motor control.…”
Section: Introductionmentioning
confidence: 99%